Comparative Cellular and In Vivo Anti-cancer studies of Doxorubicin Liposomes Prepared with Different Types of Phospholipids - Miatmoko, Andang; Cahyani, Devy Maulidya; Kawano, Kumi; Hattori, Yoshiyuki (Indonesian Journal of Pharmacy, 2024)
The selection of lipid components of membrane bilayer determines the rigidity of liposomes affecting drug efficacy, especially for cancer drug delivery. The present study evaluated liposomes with different rigidity for delivering doxorubicin (DOX). In this work, liposomes composed of rigid lipid, hydrogenated soybean phosphatidylcholine (HSPC), were totally or partially substituted with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) or 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE). The liposomes are composed of phosphatidylcholine (HSPC, POPC), with and without combination with DOPE, cholesterol, and DSPE-mPEG2000 with a molar ratio of 57: 38: 5, respectively. Liposomes were prepared using a thin layer hydration method. Then, in vitro cytotoxicity and in vivo antitumor activity of these liposomes were evaluated. Substitution of HSPC with POPC resulted in similar cytotoxicities profiles similar to the DOX solution on C26 colon cancer cells and LLC cells. The DOPE addition to DOX liposomes reduced the antitumor activity. In conclusion, the lipid substitution of HSPC with POPC or DOPE reduced liposome rigidity; however, it lowered the in vivo antitumor activity.